MRI Features of Spinal Epidural Angiolipomas - Hu, Su (The Korean Society of Radiology, 2013)
OBJECTIVE: To describe the MRI findings in ten patients of spinal epidural angiolipoma for differentiated diagnosis presurgery. MATERIALS AND METHODS: Ten surgically proved cases of spinal epidural angiolipomas were retrospectively reviewed, and the lesion was classified according to the MR findings. RESULTS: Ten tumors were located in the superior (n = 4), middle (n = 2), or inferior (n = 4) thoracic level. The mass, with the spindle shape, was located in the posterior epidural space and extended parallel to the long axis of the spine. All lesions contained a fat and vascular element. The vascular content, correlating with the presence of hypointense regions on T1-weighted imaging (T1WI) and hyperintense signals on T2-weighted imaging, had marked enhancement. However, there were no flow void signs on MR images. All tumors were divided into two types based on the MR features. In type 1 (n = 3), the mass was predominantly composed of lipomatous tissue (> 50%) and contained only a few small angiomatous regions, which had a trabeculated or mottled appear. In type 2 (n = 7), the mass, however, was predominantly composed of vascular components (> 50%), which presented as large foci in the center of the mass. CONCLUSION: Most spinal epidural angiolipomas exhibit hyperintensity on T1WI while the hypointense region on the noncontrast T1WI indicates to be vascular, which manifests an obvious enhancement with gadolinium administration.